Perspektif Islam Dalam Pendidikan Yang Ideal Bagi Kehidupan Manusia - Juhra, Al (Indonesian Journal of Teaching and Teacher Education, 2023)
Education is an effort that is carried out regularly and systematically, carried out by people who are responsible for influencing children to have characteristics and habits in accordance with educational ideals, in other words education is assistance given deliberately to children, in physical and spiritual growth to reach the adult level. Pragmatically, education must be carried out ideally, in accordance with applicable rules, both formatively and religiously, so that education is not separated between general and religious. The purpose of this writing is to provide a view of the ideal education of human education in terms of Islamic education, so that there is an integration of education in life. The method used in this writing is qualitative descriptive concept analysis. The result of this writing is the descriptive descriptive description of the ideal education for humans according to the Islamic view, namely education based on the Qur'an and Hadith. So that the implication of education based on the Quran and Hadith is the integration of science in living in this world.